Pengaruh Kontrasepsi Suntik DMPA Terhadap Kenaikan Berat Badan Tikus Betina Galur Wistar - Dwi Retna Prihati (Jurnal Kebidanan dan Kesehatan Tradisional, 2018)
Abstract: DMPA Injectable Contraception, Body Weight. The purpose of this study to determine the effect of contraception DMPA injection to BB in female blood wistar strain female. The benefits of this study are expected to increase public knowledge about injectable contraception especially related to the side effects of weight gain. This type of research is an experimental laboratory. Research design Randomized pre-post test group with control, the sample size of 10 adult female mice Wistar strain divided into 2 groups. Data were analyzed by independent T test. Significant value of p <0.05. The result of this research is there is significant difference between control group and DMPA contraception treatment group (p = 0,008). In conclusion contraceptive DMPA affects body weight wistar female rat strain.